Curvas de suportabilidade dielétrica e térmica para televisores integradas ao APR e ao banco de dados da Cemig Distribuição S.A - Ávila, Claudinei Jeremias de (2011)
Aneel Ordinance No. 414 of September 9, 2010, guarantees the right to consumers of electricity supplied at a voltage equal to or less than 2.3 kV, in case of damage caused by disruption occurred in the system, replacement of damaged electrical equipment, installed in consumer units, operating in the same condition found prior to the occurrence or, alternatively, compensation in cash equivalent to that required to make it return to that condition, or even replaced with equivalent equipment, regardless of fault of the concessionaire. The consumer has up to 90 (ninety) days from the date of the likely occurrence of lightning damage to equipment, to request reimbursement to the distributor, and provide at least the following elements, according to the ordinance above: I - likely date and time the damage occurred; II - information showing that the applicant is the holder of the consumer unit, or his legal representative; III - report of the problem presented by electrical equipment, and IV - Description and general characteristics of the damaged equipment, such as brand and model. The same decree states that the distributor should investigate the existence of causation, even considering the records of occurrences in your network and must inform the consumer the result of the reimbursement request in writing within 15 (fifteen) days from the date of the check or, failing that, from the date of the request for reimbursement. Also in case of refusal, the distributor must provide the consumer with a standardized application form in writing, containing at least the detailed reasons for the rejection. Due to the complexity of the analysis of power system disturbances propagated by the concessionaire and the lack of tools to support such analysis, what we see today are simplistic analysis, often based on technical reports from an authorized dealer, which suggests a possible origin for the defect. The concessionaire will often choose to make the compensation to avoid wear and image conflicts with their customers. Thus, given the new demands of the current ordinance, the need to establish a scientific methodology and easy operation, the growing number of complaints and a high cost of claims paid, utilities have invested in research R & D from scientific institutions to obtain procedures that can contribute to a more transparent, fair and scientific basis for this scenario. That said, this dissertation has met the needs listed above, proposing a methodology for examining applications for reimbursements of televisions based on the new curves and dielectric withstand unprecedented thermal curves, integrating quickly and easily to the geo-referenced database the system\'s electrical utility Cemig SA, culminating in a software for easy operation.